2016
DOI: 10.1371/journal.pone.0154448
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study on the Seedless Phenotype in Banana (Musa spp.) Reveals the Potential of a Selected Panel to Detect Candidate Genes in a Vegetatively Propagated Crop

Abstract: Banana (Musa sp.) is a vegetatively propagated, low fertility, potentially hybrid and polyploid crop. These qualities make the breeding and targeted genetic improvement of this crop a difficult and long process. The Genome-Wide Association Study (GWAS) approach is becoming widely used in crop plants and has proven efficient to detecting candidate genes for traits of interest, especially in cereals. GWAS has not been applied yet to a vegetatively propagated crop. However, successful GWAS in banana would conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 64 publications
2
71
2
Order By: Relevance
“…Access to large-scale sequence and phenotype information at unprecedented scales is providing new opportunities to accelerate the application of basic research. This includes the ability to formulate testable hypotheses about the genetic architecture of quantitative variation, the genes and biological pathways involved, and the causal variants responsible for the inheritance of complex traits in diverse species (Hamblin et al, 2011;Lipka et al, 2015;Sardos et al, 2016;Yano et al, 2016). It should be noted that raw sequence information, if it is to be correctly interpreted and exploited, needs to be integrated with an intimate knowledge of the biology of the species under consideration, the phenotype or performance of the individuals or population that has been sequenced, and the agro-ecosystem in which they have been grown, including the cultural context and farmers' management practices.…”
Section: The Challenges That Must Be Overcome To Realise Emerginmentioning
confidence: 99%
“…Access to large-scale sequence and phenotype information at unprecedented scales is providing new opportunities to accelerate the application of basic research. This includes the ability to formulate testable hypotheses about the genetic architecture of quantitative variation, the genes and biological pathways involved, and the causal variants responsible for the inheritance of complex traits in diverse species (Hamblin et al, 2011;Lipka et al, 2015;Sardos et al, 2016;Yano et al, 2016). It should be noted that raw sequence information, if it is to be correctly interpreted and exploited, needs to be integrated with an intimate knowledge of the biology of the species under consideration, the phenotype or performance of the individuals or population that has been sequenced, and the agro-ecosystem in which they have been grown, including the cultural context and farmers' management practices.…”
Section: The Challenges That Must Be Overcome To Realise Emerginmentioning
confidence: 99%
“…Indeed, Sardos et al. () observed the challenges in generating precise GWAS results in their study on banana. Thus, an accurate method of investigation in a suitable time and having many cumulative phenotype data about the necessary trait are critical for obtaining reliable GWAS results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, differences in the trait estimation method and environmental factors affecting the fruits give rise to uneven phenotype data, which result in drastic deviation among samples (Migicovsky et al, 2016), leading to data not being accumulated and being of poor quality and quantity. Indeed, Sardos et al (2016) observed the challenges in generating precise GWAS results in their study on banana. Thus, an accurate method of investigation in a suitable time and having many cumulative phenotype data about the necessary trait are critical for obtaining reliable GWAS results.…”
Section: Importance Of Phenotype Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically, parthenocarpy may happen due to a single partially dominant gene as in cucurbits (Kim et al, 1992; Menezes et al, 2005) or due to a single recessive gene as in sweet pepper (Tiwari et al, 2011) or due pleiotropy of major and minor genes as in brinjal/eggplant (Miyatake et al, 2012). In case of banana, parthenocarpy is hypothesized (Sardos et al, 2016) to be due to a major dominant gene ( P or P1 ) interacting with minor ones (Simmonds, 1953). With decoding of structural genome of banana, discovery of the precise mechanism of parthenocarpy will give a boost to quality fruit production in commercial plantation.…”
Section: Parthenocarpymentioning
confidence: 99%